The Influence of Perceived Ease and Usefulness on the Decision to Use Qris as a Digital Payment Tool: JEL Classification: D12, E42, G21, O33, M31 - Aini, Ruqyal; Sapwan, Muhammad; Andriani, Yuyun (Newinera Publisher, 2025)
Digital technology is fast evolving, which has led to a change of cash payment to non-cash payment. A good example of this innovation that Bank Indonesia brought about is the Quick Response Code Indonesian Standard (QRIS). The aim of the present study is to focus on the relationship linking between the perception of ease of use and the perception usefulness with consumer adoption of QRIS in Cafes Bento Mataram. The data were obtained through the questionnaire of the structured questionnaire that was distributed to the consumers of Café Bento Mataram. The respondents were 100 in number and they were chosen randomly. The obtained data were then analysed with the help of SPSS version 25. This analysis involved reliability and validity, classical assumptions tests, and parametric tests such as t -tests, F-tests and coefficient of determination (R) calculations, among various procedures of multiple regression. The findings reveal that the perceived ease of use has a positive and statistically significant effect on the decision to adopt QRIS with a t -statistic of 4.704, which is above the critical value of 1.661 (p = 0.000 0.05). Perceived usefulness also has positive significant value with t-statistic of 6.441 exceeding critical value of 1.661 (p=0.000<0.05). These results suggest that consumers who consider QRIS simpler and more advantageous have a higher tendency of using the system. The implications of the findings on the practical side of digital financial service providers are to improve the quality of services, their access, and benefits to the consumers to increase their acceptance of the use of QRIS.